Organised sexual abuse - Salter, Michael (A GlassHouse book, 2013)
1. A subject of smoke and mirrors : understanding organised abuse -- 2. Organised abuse cases : network, institutional, familial and ritual -- 3. The historical context : liberalism, libertinism and ideologies of masculine sexuality -- 4. Organised abuse and the pleasures of disbelief -- 5. Down the rabbit hole : my story -- 6. The experiences of survivors : extraordinary crimes in everyday life -- 7. Living in two worlds : familial organised abuse -- 8. Sadistic abuse : control, violence and pleasure in organised abuse -- 9. Ritual and torture in organised abuse -- 10. Sexual murder and reproductive harm : the outer limits of organised sexual abuse.